Associations of novel adipocytokines with bone biomarkers in intra uterine growth-restricted fetuses/neonates at term. (28th October 2013) - Briana, Despina D.; Boutsikou, Maria; Boutsikou, Theodora; Malamitsi-Puchner, Ariadne
Abstract: Objective : To prospectively investigate the potential associations of the novel adipocytokines resistin, apelin and visfatin (recently implicated in bone metabolism) with bone biomarkers in fetal and neonatal blood from intra uterine growth restricted (IUGR, associated with low bone mass at birth) and appropriate for gestational age (AGA) pregnancies. Methods : Circulating concentrations of resistin, apelin and visfatin were correlated with concentrations of markers of bone formation [osteocalcin (OC), bone-specific alkaline phosphatase (BALP)] and resorption [osteoprotegerin (OPG), soluble receptor activator of nuclear factor-κB ligand (sRANKL) and cross-linked N-telopeptide of type I collagen (NTx)] in 20 IUGR and 20 AGA full-term fetuses and neonates on postnatal day 1-(N1) and 4-(N4). Results : In the AGA group, fetal resistin and N1 visfatin concentrations negatively correlated with respective NTx ones ( r  ≥ −0.472, p  ≤ 0.036 in both cases). In the IUGR group, fetal and N4 resistin concentrations negatively correlated with sRANKL concentrations ( r  ≥ −0.583, p  ≤ 0.007 in both cases). Furthermore, fetal apelin and visfatin concentrations positively correlated with fetal BALP ones ( r  ≥ 0.471, p  ≤ 0.042, in both cases). Conclusions : All three adipocytokines may exert a positive effect on fetal/neonatal bone metabolism, either by inhibiting bone resorption or promoting bone formation in both normal and IUGR pregnancies. Although the mechanisms behind these correlations are unclear, a modulation of perinatal bone metabolism by these adipocytokines may be suggested.